Gold-Catalyzed Cyclization/Intermolecular Methylene Transfer Sequence of O-Propargylic Oximes Derived from Glyoxylates - Gima, Shinya; Shiga, Keigo; Terada, Masahiro; Nakamura, Itaru (Synlett, 2019)
We successfully extended our gold-catalyzed skeletal rearrangement reaction of O-propargylic oximes through C=N bond cleavage to include substrates having an ester group on the oxime moiety, affording the corresponding 2-isoxazolines having an alkoxycarbonylmethylene group at the 4-position in good to high yields. Our mechanistic studies indicated that the transfer of the alkoxycarbonylmethylene group proceeded in an intermolecular manner, confirming that the reaction proceeds through cyclization followed by intermolecular transfer of the alkoxycarbonylmethylene group.
Keywords: gold catalysis; rearrangement; heterocycles; cyclization; progargylic oximes; isoxazolines